OPPORTUNITIES FOR DEVELOPING SPEAKING SKILLS IN OUT-OF-COURSE TRAININGS USING DIGITAL TECHNOLOGIES (Universal International Scientific Journal, 2026)
This article analyzes the didactic and methodological possibilities of developing students' oratory skills in extracurricular activities using modern digital technologies. The article reveals mechanisms for developing oratory skills through the use of Prezi, Padlet, Canva, Zoom, CapCut, Telegram, YouTube and other digital tools in education. At the same time, it also highlights strategies for their implementation in practice, ways to strengthen communication between teachers and students, and the advantages of digital assessment systems.
Keywords: public speaking skills, digital technologies, extracurricular activities, communicative competence, digital assessment, educational effectiveness